The Great Seljuk Empire - Peacock, A. C. S. (The Edinburgh history of the Islamic empires, 2015)
Chapter 1. The Rise of the Seljuk Empire: from the Eurasian Steppe to the Gates of Cairo, c. 965-1092; Chapter 2. Crisis, Consolidation and Collapse: the Great Seljuk Empire and the Sultanate of Iraq, 1092-1194; Chapter 3. Sovereignty, Legitimacy and the Contest with the Caliphate; Chapter 4. The Dargah: Courts and Court Life; Chapter 5. The Kuttab: Bureaucrats and Administration; Chapter 6. The 'Askar: The Seljuk military; Chapter 7. Religion and the Seljuk Empire; Chapter 8. The Economic and Social Organisation of the Seljuk Empire; Conclusion: The Seljuk Legacy; Appendices: Regnal Dates of Seljuk Sultans; 'Abbasid Caliphs, Khwarazmshahs and principal Atabegs; Genealogical chart of the Seljuk Sultans; Chronological Outline; Glossary; Bibliography.